2017
DOI: 10.1111/ibi.12493
|View full text |Cite
|
Sign up to set email alerts
|

No short‐ or long‐term effects of geolocator attachment detected in Pied Flycatchers Ficedula hypoleuca

Abstract: Tracking small passerines using miniaturized location tags is a rapidly expanding field of study. In a 1-year study, we tested whether there were any short-or longer-term effects of fitting geolocators weighing 3% of body mass on male Pied Flycatchers Ficedula hypoleuca. In the deployment year, we compared adult provisioning rates to nestlings, nestling growth and nest success between nesting attempts in which adult males were fitted with a geolocator, with control nests where males had the same capture histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…This conclusion is supported by results obtained on two species of swallows by Fairhurst et al (2015), who observed that, despite the clear negative effect of geolocators on return rate, returning individuals had similar stress levels (as measured by corticosterone levels in feathers) compared to control ones. Similar observations come from other studies on species where surviving geolocator birds seemed not to differ in migration or breeding performance compared to control birds (Rodriguez et al 2009, Peterson et al 2015, Matyjasiak et al 2016, van Wick et al 2016, Bell et al 2017, although geolocator birds suffered higher inter-annual mortality (Raybuck et al 2017). In a meta-analysis of the effect of geolocators on shorebirds, the simple presence of the device was the most significant factor affecting return rates and hatching success (Weiser et al 2016).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This conclusion is supported by results obtained on two species of swallows by Fairhurst et al (2015), who observed that, despite the clear negative effect of geolocators on return rate, returning individuals had similar stress levels (as measured by corticosterone levels in feathers) compared to control ones. Similar observations come from other studies on species where surviving geolocator birds seemed not to differ in migration or breeding performance compared to control birds (Rodriguez et al 2009, Peterson et al 2015, Matyjasiak et al 2016, van Wick et al 2016, Bell et al 2017, although geolocator birds suffered higher inter-annual mortality (Raybuck et al 2017). In a meta-analysis of the effect of geolocators on shorebirds, the simple presence of the device was the most significant factor affecting return rates and hatching success (Weiser et al 2016).…”
Section: Discussionsupporting
confidence: 69%
“…Overall, it seems established that smaller species and aerial foragers suffer the most from carrying geolocators (Fairhurst et al 2015; but see Matyjasiak et al 2016 for lack of short-term effects on flight performance). On the other hand, evidence exists that several small-sized, highly migratory species did not suffer detectable effects of carrying a geolocator (Pakanen et al 2015, Peterson et al 2015, Blackburn et al 2016, van Wijk et al 2016, Bell et al 2017). These contrasting findings suggest that species-specific traits and features of the devices can determine large variation in the size of the detrimental effects of tracking devices.…”
Section: Introductionmentioning
confidence: 99%
“…Our failure to retrieve nasal-saddle geolocators prevented us from comparing the quality of data recorded vs. legband mounts. Nonetheless, leg-band geolocators provided light-level readings of sufficient quality to estimate stopover locations, and we detected no difference in recovery rate for canvasbacks marked with standard metal bands vs. those with leg-band-mounted geolocators, weakly suggesting no adverse effect of legmounted geolocators on survival rates (consistent with other studies; Bell et al 2017). Finally, when deployed on female birds, leg band-mounted geolocators have the additional advantage of estimating the timing and duration of reproductive bouts (shading of light detectors because of incubation activities can be easily detected; Burger et al 2012;Gosbell et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Despite their promise, any information gained by geolocator deployment must be balanced against the possibility of detrimental effects to the animals studied. Although several studies have examined the effects of geolocators on return rates for larger birds [1114], relatively few have looked at effects on return rates in the smallest birds that can currently be tracked with these devices (but see [7, 9, 15]).…”
Section: Introductionmentioning
confidence: 99%